Body composition of female air force personnel: a comparative study of aircrew, airplane, and helicopter pilots (2022)
This research aimed to analyze the body composition (BC) of different groups of women aircrew units in the Spanish Air Forces for a better understanding and improvement of their operability. Specifically, 184 female aircrew members were analyzed and classified into specialties (38 airplane pilots, age: 32.8 ± 10.8; 26 helicopter pilots, age: 32.0 ± 9.18; and 120 transport aircrew, age: 36.9 ± 8.18). The women’s BC was analyzed with an InBody720 bioimpedance device previously used in the military population. There were differences in the BC among specialties, although there were similarities between airplane and helicopter pilots. Airplane (24.0% ± 10.4%) and helicopter pilots (22.6 ± 6.32%) had a smaller percentage of body fat mass than transport aircrew (26.3 ± 7.51%), but there was uniformity among groups in skeletal muscle mass and soft lean mass. We found no differences in body water among specialties. Differences in BCs were previously reported for men in the air force, and these results in women showed similarities for different job entry requirements, different training needs, and different occupational behaviors among units in the Air Force. These results help to deepen the previous knowledge of women’s BC standards in military units. Although pilots are primarily responsible for the aircraft, healthy habits should be encouraged to keep fit and improve the performance of all aircrew members both in flight and when they are deployed.